STUDI PEMAHAMAN BLOK RANGKAIAN PENERIMA PADA TELEVISI TRAINER - Amir, Ardi (MEKTEK, 2011)
"Television" is no longer a novelty to the community, especially the urban areas. At first only intended as amedium of television to broadcast information and entertainment that comes with moving images such as ascene. However the line with technological developments lead to the use of television not only as the meansmentioned above. Today television is also used as an advertising medium, video games, computer monitorsand others. Ukurannyapun been diverse, ranging in size from big screen to small screen size.Therefore it is no exaggeration to say that television is very useful trainer for anyone who wants to knowmore about a television set, because the TV Trainer can be known about a block diagram, the workings ofeach block and the damage that occurs if visible symptoms are not normal in a television receiver